‘I Just Stopped Going’: A Mixed Methods Investigation Into Types of Therapy Dropout in Adolescents With Depression - O’Keeffe, Sally; Martin, Peter; Target, Mary; Midgley, Nick (Frontiers in Psychology, 2019)
What does it mean to ‘drop out’ of therapy? Many definitions of ‘dropout’ have been proposed, but the most widely accepted is the client ending treatment without agreement of their therapist. However, this is in some ways an external criterion that does not take into account the client’s experience of therapy, or reasons for ending it prematurely. This study aimed to identify whether there were more meaningful categories of dropout than the existing dropout definition, and to test whether this refined categorisation of dropout was associated with clinical outcomes. This mixed-methods study used a subset of data from the IMPACT trial, which investigated psychological therapies for adolescent depression. Adolescents were randomly allocated to a treatment arm (Brief Psychosocial Intervention; Cognitive-Behavioural Therapy; Short-Term Psychoanalytic Psychotherapy). The sample for this study comprised 99 adolescents, aged 11-17 years. 32 were classified as having dropped out of treatment and participated in post-therapy qualitative interviews about their experiences of therapy. For 26 dropout cases, the therapist was also interviewed. 67 cases classified as having completed treatment were included to compare their outcomes to dropout cases. Interview data for dropout cases were analysed using ideal type analysis. Three types of dropout were constructed: ‘dissatisfied’ dropout, ‘got-what-they-needed’ dropout, and ‘troubled’ dropout. ‘Dissatisfied’ dropouts reported stopping therapy because they did not find it helpful. ‘Got-what-they-needed’ dropouts reported stopping therapy because they felt they had benefitted from therapy. ‘Troubled’ dropouts reported stopping therapy because of a lack of stability in their lives. The findings indicate the importance of including the perspective of clients in definitions of drop out, as otherwise there is a risk that the heterogeneity of 'dropout' cases may mask more meaningful distinctions. Clinicians should be aware of the range of issues experienced by adolescents in treatment that lead to disengagement. Our typology of dropout may provide a framework for clinical decision-making in managing different types of disengagement from treatment.